The Effect of Postoperative Antithrombin Supplementation on the Inflammatory and Coagulation Status of a Surgically Treated Patient With a Malignant Tumor in the Small Pelvis—Case Series - Ranko Lazović; Ognjenka Šarenac (Cancer Reports, 2025)
ABSTRACT Introduction Antithrombin has the function of a natural anticoagulant. It is the main component of the inhibitory anticoagulant system, which, under physiological conditions, opposes the procoagulant mechanisms of hemostasis, preventing the occurrence of a hypercoagulable state, the development of thrombosis, and thromboembolic complications. Antithrombin deficiency, acquired or congenital, leads to the development of a hypercoagulable state and thromboembolic complications. Antithrombin also has a significant anti‐inflammatory, antimicrobial, and antitumor effect. Patients with malignant diseases are often in a hypercoagulable and proinflammatory state due to the nature of the disease itself and the fact that they undergo extensive surgical procedures and chemotherapy as therapeutic modalities. Therapeutic supplementation with antithrombin products could establish normal coagulability and reduce or suppress the inflammatory response. However, previous randomized studies have not shown a long‐term benefit of this approach. Case In our female patients who underwent multiple organ resections, with advanced colorectal cancer and acute pancreatitis treated surgically, with a pronounced inflammatory and hypercoagulable response on the first postoperative day, antithrombin supplementation in the first four postoperative days contributed to the establishment of normal coagulability confirmed by the ROTEM analysis while suppressing the inflammatory response followed by inflammatory laboratory parameters. Conclusion Compensating for the antithrombin deficit in the first four postoperative days may benefit the specified patient group, with careful monitoring of hemostatic and inflammatory parameters.